2021
DOI: 10.1002/jssc.202100802
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extraction process of flavonoids from Trollius ledebouri with natural deep eutectic solvents

Abstract: In recent years, natural deep eutectic solvents have been favored greatly due to their environment friendly, mild biological toxicity and simple biodegradability. Natural deep eutectic solvents gradually applied for the extracting bioactive compounds from natural products efficiently. In this study, 20 natural deep eutectic solvents were prepared and their physical and chemical properties were tested. The ultrasonic-assisted extraction method was used to extract flavonoids from Trollius ledebouri and high-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, further increasing the extraction temperature (>70 • C) does not improve the extraction efficiency. In addition, the reaction system generates too much heat energy at high extraction temperatures, which may lead to the degradation of unstable substances and thus reduce the extraction yield [32]. Therefore, the extraction temperature was set at 70 • C in the following experiments.…”
Section: Single Factor Experiments Resultsmentioning
confidence: 99%
“…However, further increasing the extraction temperature (>70 • C) does not improve the extraction efficiency. In addition, the reaction system generates too much heat energy at high extraction temperatures, which may lead to the degradation of unstable substances and thus reduce the extraction yield [32]. Therefore, the extraction temperature was set at 70 • C in the following experiments.…”
Section: Single Factor Experiments Resultsmentioning
confidence: 99%
“…The β Co/Ni increases with the growth of T e . The reason is that higher temperature reduces the viscosity and surface tension of the extraction system, which is beneficial to mass transfer [ 37 ]. In addition to this, the extraction reaction of Co 2+ using extractant of [C 4 H 9 NH 3 ][Cyanex 272] is an endothermic reaction, and the higher T e is conductive to the reaction [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the single-factor experimental results, three independent factors, i.e., pH ini (A), t e (B), and T e (C), were found to be responsible for the β Co/Ni . With the aim of analyzing the A, B, and C, three-factor and three-level Box–Behnken experimental design was used to conduct response surface analysis [ 37 ], and the three factors were optimized at three levels (−1, 0, −1) ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the following years, Choi et al introduced natural DES(NADES)consisting of natural product components for these mixtures in 2011, which has led to the development of DESs as a greener solvent [20,21]. It has been shown that the DESs chosen as extraction solvents are not only green but that DESs can also improve the extraction efficiency of bioactive compounds [22][23][24]. Therefore, DESs have gradually gained attention as a new type of green solvent [25,26].…”
Section: Introductionmentioning
confidence: 99%